Retrofitting suburbia case studies : urban design strategies for urgent challenges - Dunham-Jones, Ellen, 1959-; Williamson, June (Hoboken : Wiley, 2020)
"Change is everywhere in the suburbs of northern America, the built landscapes where most residents of the United States and Canada live. Speculative visions of futuristic solar suburbs powering electric cars and e-bikes make headlines at the same time that mid-century modern ranch house renovations are all the rage. Exurban McMansions fill with multi-generational families while infill housing and backyard cottages meet the needs of smaller households in inner suburban neighborhoods. Established suburbs largely built for young white families are more likely to be populated today by older white faces and younger faces of color"--
Includes bibliographical references.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Suburbs -- North America -- Planning; City planning -- North America; Sustainable urban development -- North America